Hepatic Presentation of Late-Onset Multiple Acyl-CoA Dehydrogenase Deficiency (MADD): Case Report and Systematic Review - Siano, Maria Anna; Mandato, Claudia; Nazzaro, Lucia; Iannicelli, Gennaro; Ciccarelli, Gian Paolo; Barretta, Ferdinando; Mazzaccara, Cristina; Ruoppolo, Margherita; Frisso, Giulia; Baldi, Carlo; Tartaglione, Salvatore; Di Salle, Francesco; et al. (Frontiers in Pediatrics, 2021)
Diagnosis of pediatric steatohepatitis is a challenging issue due to a vast number of established and novel causes. Here, we report a child with Multiple Acyl-CoA Dehydrogenase Deficiency (MADD) presenting with an underrated muscle weakness, exercise intolerance and an atypically severe steatotic liver involvement. A systematic literature review of liver involvement in MADD was performed as well. Our patient is a 11-year-old otherwise healthy, non-obese, male child admitted for some weakness/asthenia, vomiting and recurrent severe hypertransaminasemia (aspartate and alanine aminotransferases up to x 20 times upper limit of normal). Hepatic ultrasound showed a bright liver. MRI detected mild lipid storage of thighs muscles. A liver biopsy showed a micro-macrovacuolar steatohepatitis with minimal fibrosis. Main causes of hypertransaminasemia were ruled out. Serum aminoacids (increased proline), acylcarnitines (increased C4-C18) and a large excretion of urinary glutaric acid, ethylmalonic, butyric, isobutyric, 2-methyl-butyric and isovaleric acids suggested a diagnosis of MADD. Serum acylcarnitines and urinary organic acids fluctuated overtime paralleling serum transaminases during periods of illness/catabolic stress, confirming their recurrent nature. Genetic testing confirmed the diagnosis [homozygous c.1658A>G (p.Tyr553Cys) in exon 12 of the ETFDH gene]. Lipid-restricted diet and riboflavin treatment rapidly ameliorated symptoms, hepatic ultrasonography/enzymes, and metabolic profiles. Literature review (thirty-seven retrieved eligible studies, 283 patients) showed that liver is an extramuscular organ rarely involved in late-onset MADD (70 patients), and that amongst forty-five patients who had fatty liver only nine had severe presentation. Conclusion. MADD is a disorder with a clinically heterogeneous phenotype. Our study suggests that MADD warrants consideration in the work-up of obesity-unrelated severe steatohepatitis.